Does the order of factors affect the product? Lessons learned from the TORCH trial - Skarbnik, Alan P; Olszanski, Anthony J (Translational Lung Cancer Research; Vol 2, No 1 (February 14, 2013): Translational Lung Cancer Research, 2012)
Lung cancer is the leading cause of cancer-related deaths globally, with a low 5-year survival rate [approximately 15 percent - NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines). non-small cell lung cancer. National Comprehensive Cancer, Network 2012]. Non-small cell lung cancer (NSCLC) is the most common subtype. Traditionally, platinum-based chemotherapy has been the main frontline treatment modality for advanced NSCLC (1). Despite the many active combination chemotherapy regimens, median overall survival (OS) for advanced NSCLC remains 10-12 months.